Modulation of blood redox status by the progression of induced apical periodontitis in rats - Frazão, Deborah Ribeiro; Santos Mendes, Paulo Fernando; Baia-da-Silva, Daiane Claydes; Mendonça de Moura, João Daniel; Neves dos Santos, Vinicius Ruan; Matos-Sousa, José Mario; de Souza Balbinot, Gabriela; Guimarães, Douglas Magno; Collares, Fabrício Mezzomo; Lima, Rafael Rodrigues (Frontiers in Physiology, 2023)
Thus, this study aimed to investigate if apical periodontitis in different periods changes systemic levels of the antioxidant and pro-oxidant parameters in Wistar rats. Twenty-four rats were randomly allocated into healthy animals, apical periodontitis at 14 days (AP14) and apical periodontitis at 28 days (AP28). The first mandibular molars were accessed in the AP groups, and the pulp chamber was exposed to the oral environment, inducing the apical lesion. After 14 and 28 days, the animals were anesthetized, euthanized, and hemimandibles were collected for micro-computed tomography (micro-CT) analysis to measure lesion volume, bone volume (BV), percent of bone to total tissue volume (BV/TV), trabecular thickness (Tb.Th), trabecular number (Tb.N), and trabecular space (Tb.Sp). A histological examination of the remaining bone was also performed. Finally, blood samples were collected for oxidative biochemistry analysis, investigating glutathione (GSH), Trolox equivalent antioxidant capacity (TEAC), and lipid peroxidation (TBARS). The lesion volume was greater at 28 than at 14 days, as shown by micro-CT. AP14 and AP28 had decreased BV and Tb.Th, but only AP28 showed a reduction in BV/TV. Tb.N and Tb.Sp were increased in apical periodontitis at 28 days. In the histopathological analysis, AP14 had focal regions of moderate mononuclear inflammatory infiltrate, and AP28 had an intense inflammatory infiltrate with bacterial colonies. In the biochemical evaluation, GSH, TEAC, and TBARS were increased after 14 days. However, GSH returned to control levels, TEAC was similar to AP14, and TBARS increased significantly after 28 days. Therefore, the oxidative biochemistry response was modulated according to the progression of periapical damage. After 14 days, the organism could still react to the injury. However, at 28 days, the antioxidant response decreased, associated with an increase in TBARS.